Hemoglobinopathies profile in pregnant women: spatial distribution and temporal analysis from 2013 to 2019 in the State of Piauí, Brazil (Research, Society and Development, 2022)
This article aims to identify the profile of hemoglobinopathies in pregnant women diagnosed during prenatal care in the State of Piauí through spatial distribution and temporal analysis based on data from a public health laboratory. The study analyzed the results of pregnant patients at the Piauí Central Public Health Laboratory from January 2013 to December 2019. In all, 39,616 hemoglobinopathy research exams were performed; 2,480 (6.26%) of the pregnant women tested positive for hemoglobinopathies. There was a prevalence of pregnant women with Hb AS (73.63%) and Hb AC (10.56%); the sickle cell disease genotypes were Hb SC: 5.48%, Hb SF: 0.77% and Hb SS: 0.44%; less prevalent variant hemoglobins: Hb AE (0.12%), Hb AF (0.08%) and Hb CC (0.04%). Most of the pregnant women identified with hemoglobinopathies were aged between 13 and 25 years and were located in the central-northern piauiense mesoregion. The temporal analysis revealed slight percentage changes over the years and obtained a higher rate in 2018 with 6.7% of pregnant women diagnosed. The spatial distribution identified variant hemoglobins in 56 municipalities, among them, Teresina, União, José de Freitas, Bom Jesus, Oeiras and Valença do Piauí had the highest number of cases. The results obtained indicate the potential risk of sickle cell trait and hemoglobin C trait among pregnant women in different regions of Piauí, increasing the probability of newborns with the disease, whether homozygous or heterozygous, reflecting an important public health issue in the State.